Gambaran Epidemiologi Deskriptif Tuberkulosis di Wilayah Kerja Puskesmas Dobo Tahun 2016-2019 - Bellytra Talarima; Ivy Violan Lawalata; Novalia B. Mantayborbir (FORIKES, 2021)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Such germs typically enter the human body through breathing air into the lungs. From the Global Tuberculosis Report 2018 there are nine countries with highest burden of tuberculosis in the world that is India, China, Indonesia, Philippines, Pakistan, Nigeria, Bangladesh and South Africa. Purpose to find out the descriptive epidemiology of tuberculosis in tuberculosis patients in Dobo Health Center, Aru Islands District 2016-2019. This type of research was observational with a descriptive design regarding the epidemiology of tuberculosis according to people, time and place, data analysis using univariat analysis. This research was carried out at the Dobo Health Center, Aru Islands District during 05 to 18 September 2019 with a population of 208 cases. The results showed that, based on their age group, most tuberculosis patients were in the 15-64 age group, 170 (81.7%), the most sex is in male 118 (56.7%), tuberculosis was most classified in pulmonary tuberculosis 178 (85.5%), most treatment outcome was 98 complete treatments (47.1%), highest marital status is 141 marriages (67.8%), most jobs are as farmers/fishermen 89 (42.8%, duration of treatment is 6 months treatment 146 (70.2%). Based on place namely siwalima village 93 (44.7%). Descriptive epidemiological description of tuberculosis at the Dobo Health Center in 2016-2019 was more productive, male, classified pulmonary tuberculosis, treatment results were complete treatment, married status, farmer/fisherman occupation, duration of treatment 6 months, located in Siwalima Village. Keywords: tuberculosis; descriptive epidemiology; person; time; place ABSTRAK Tuberkulosis (TB) adalah suatu penyakit menular yang disebabkan oleh mycobacterium tuberculosis. Kuman tersebut biasanya masuk ke dalam tubuh manusia melalui udara pernafasan ke dalam paru. Laporan Global Tuberculosis Report 2018 terdapat sembilan negara dengan beban tuberkulosis tertinggi di dunia yaitu India, Cina, Indonesia, Filipina, Pakistan, Nigeria, Bangladesh dan Afrika Selatan. Tujuan untuk mengetahui gambaran epidemiologi deskriptif penyakit tuberkulosis padapenderita tuberkulosis di Puskesmas Dobo Kabupaten Kepulauan Aru tahun 2016-2019. Jenis penelitian observasional dengan rancangan deskriptif mengenai gambaran epidemiologi tuberkulosis menurut orang waktu dan tempat. Analisis data menggunakan analisis univariat. Penelitian ini dilaksanakan di Puskesmas Dobo, Kabupaten Kepulauan Aru selama tanggal 05 - 18 September 2019. Hasil penelitian menunjukkan bahwa berdasarkan kelompok umur, penderita tuberkulosis paling banyak adalah kelompok umur 15-64 yaitu 170 (81,7%), jenis kelamin paling banyak pada laki-laki 118 (56,7%), klasifikasi tuberkulosis paling banyak pada tuberkulosis paru 178 (85,5%), hasil pengobatan yang paling banyak adalah pengobatan lengkap 98 (47,1%, status perkawinan paling banyak adalah kawin 141 (67,8%), pekerjaan paling banyak adalah sebagai petani/nelayan 89 (42,8%) dan lama pengobatan yaitu pengobatan 6 bulan 146 (70,2%). Tempat yaitu Kelurahan Siwalima 93 (44,7%). Gambaran epidemiologi deskriptif penyakit tuberkulosis di Puskesmas Dobo tahun 2016-2019 lebih banyak berusia produktif, berjenis kelamin laki-laki, klasifikasi tuberkulosis paru, hasil pengobatan yaitu pengobatan lengkap, berstatus kawin, pekerjaan petani/nelayan, lama pengobatan 6 bulan, bertempat di Kelurahan Siwalima.Kata kunci: tuberkulosis; epidemiologi deskriptif; orang; waktu; tempat